Allergic rhinitis in Chinese young adults from the Singapore/Malaysia cross-sectional genetics epidemiology study (SMCGES) cohort: Prevalence, patterns, and epidemiology of allergic rhinitis - Wong, Ambrose Qi Yi; Lim, Jun Jie; Ng, Jun Yan; Praneeth, Malipeddi; Teo, Wei Yi; Lim, Eliza Yi Ying; Ng, Yu Ting; Sio, Yang Yie; Sri Anusha, Matta; Wong, Yi Ru *; Teh, Keng Foo *; Smyrna Moti, Rawanan Shah *; et al. (Elsevier, 2022)
Background: Allergic rhinitis (AR) is characterized by the occurrence of at least 2 symptoms of nasal itching, nasal blockage, rhinorrhea, and sneezing, when not afflicted with a cold or flu, with defined atopic sensitization demonstrated by skin prick test or specific IgE responses. Besides the detriment to standard of living and economic burden of AR, both multicentre and single-cohort studies have observed an increase in AR prevalence in Asia over time.